PCSK9 Inhibitor Therapy as an Alternative for Statin Intolerance - K. O. Shnaider; M. L. Maximov; V. A. Baranova; A. A. Nekipelova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2023)
Scientific relevance. The main cause of cardiovascular pathologies is atherosclerosis, which is secondary to lipid metabolism disorders, in particular, the accumulation of low-density lipoprotein (LDL) cholesterol. Dyslipidaemia treatment with the largest evidence base predominantly includes statins in combination therapy, but their use is limited by into lerance in some patients. Alternatively, the treatment may include proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors.Aim. The study aimed to analyse the applicability of PCSK9 inhibitors in patients with statin intolerance.Discussion. According to the literature analysis, the most common presentation of statin intolerance is statin-associated muscle symptoms. The pathogenesis of statin-associated adverse events is mainly mediated by HMGCoA reductase inhibition, treatment effects on cellular and subcellular processes and skeletal muscles, and patients' genetic makeup. The mechanism of action of PCSK9 inhibitors is entirely different and involves binding and inactivation of the PCSK9 protein, which lowers blood LDL cholesterol levels. PCSK9 inhibitors have been associated with some adverse drug reactions, most notably immunogenicity; however, PCSK9 inhibitors effectively reduce LDL levels even if patients develop antibodies.Conclusions. Therefore, PCSK9 inhibitors are a safe, well-tolerated, and effec tive therapeutic strategy for hyperlipidaemia in patients with statin intolerance.